(untitled) (International Journal of Food and Nutritional Sciences, 2024)
The aim provided seems to describe a pharmacological study evaluating the antioxidant and hepatoprotective properties of a polyherbal formulation containing extracts from Euterpe oleracea in Wistar rats. In pharmacological research, antioxidant activity refers to the ability of substances to neutralize harmful free radicals in the body, which can cause cellular damage and contribute to various diseases. Hepatoprotective activity, on the other hand, pertains to the ability of substances to protect the liver from damage or promote its healing. Polyherbal formulations combine multiple herbal extracts or ingredients, often aiming to synergistically enhance therapeutic effects. The study likely involved administering the polyherbal formulation to Wistar rats and assessing its effects on antioxidant parameters, such as levels of antioxidant enzymes or markers of oxidative stress, as well as its impact on liver health through measures like liver enzymes and histopathological examination.